The Development of Food Security Behavior Model through Environmental-Based Learning: A System Dynamics Approach - Sjaifuddin, S.; Hidayat, S.; Fathurrohman, M.; Ardie, R.; El Islami, R. A. Z. (Jurnal Pendidikan IPA Indonesia, 2019)
Food security behavior is essential to be developed through continuous development of knowledge, awareness, attitudes, values, skills, and responsibility. Utilization of system dynamics methodology in educational research in the field of food security is still limited. Thus, this research aimed to develop a model of food security behavior through environmental-based learning by utilizing a system dynamics methodology. This approach starts with defining problems dynamically, developing concepts in circular causality, identifying stocks, flows, simulating, and validating the model. Through quantification of variables involved in the development of food security behavior model, the results showed that during 6 years of simulation, environmental-based learning could improve food security behavior sustainably (from 10.60 at the beginning to 74.19 at the end of simulation year) having the growth forming an exponential curve. The increase of food security behavior occurred gradually through increasing food security attitudes (from 2.09 to 7.45), food security awareness (from 0.55 to 2.34), food security values (from 0.23 to 0.85), food security knowledge (from 1.53 to 6.17), food security skills (from 0.61 to 1.83), and food security responsibility (from 0.88 to 1.67).